An Implantable Magnetic Vascular Scaffold for Circulating Tumor Cell Removal In Vivo. Issue 50 (4th November 2022) - Yin, Zhiwei; Shi, Rui; Xia, Xin; Li, Ling; Yang, Yanxia; Li, Shengkai; Xu, Jieqiong; Xu, Yiting; Cai, Xinqi; Wang, Shen; Liu, Zhangkun; Peng, Tianhuan; et al.
Abstract: An integrated trapped device (ITD) capable of removal of circulating tumor cells (CTCs) can assuage or even prevent metastasis. However, adhesion repertoires are ordinarily neglected in the design of ITDs, possibly leading to the omission of highly metastatic CTC and treatment failure. Here a vascular‐like ITD with adhesive sites and wireless magnetothermal response to remove highly metastatic CTC in vivo is presented. Such a vascular‐like ITD comprises circumferential well‐aligned fibers and artificial adhesion repertoires and is optimized for magnetothermal integration. Continuous and repeated capture in a dynamic environment increases capture efficiency over time. Meanwhile, the heat generation of the ITD leads to the capture of CTC death owing to cell heat sensitivity. Furthermore, the constructed bioinspired ultrastructure of the ITD prevents vascular blockage and induces potential vascular regeneration. Overall, this work defines an extendable strategy for constructing adhesion repertoires against intravascular shear forces, provides a vascular‐like ITD for reducing CTC counts, and is expected to alleviate the risk of cancer recurrence. Abstract : The concept of a new type of vascular‐like ITD with artificial adhesion repertoires and a wireless magnetothermal response for high metastatic circulating tumor cell removal in vivo is proposed. The ITD implanted in the artery mainly comprises PLLA fibers encapsulated with FeCo@G and a 3D structure with HA and gelatin for the preparation of bioinspired adhesive sites.